PENDAMPINGAN LITERASI HALAL BAGI TENAGA PENDIDIK, ORANG TUA, DAN PEDAGANG SEKITAR TK ABA KECAMATAN KEDUNGKANDANG - Muslikhati Muslikhati; Rahmad Hakim (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2021)
Purpose of the study: The purpose of this activity is that the educators of ABA Kindergarten in Kedungkandang sub-district can understand and understand that consumers have the right to consume halal products and convey this information to students. Methodology: The method used is mentoring which includes socialization, training, practice, monitoring, and evaluation. Main Findings: Educators, parents, food and beverage traders and students can choose safe and healthy food ingredients for consumption in accordance with Islamic rules, namely halal and thoyyib. Applications of this study: This service is useful for educators, parents and traders in choosing halal and thoyyib food and drinks for the younger generation, especially early childhood (pre-school). Novelty/Originality of this study: By using socialization, practice, monitoring, and evaluation, it increases the understanding of educators, parents and traders in choosing halal and thoyyib food and drinks.